Otwarte innowacje jako model interaktywnego zarządzania innowacjami: Open innovation as a model of interactive innovation management - Rojek, Danuta (Management and Administration Journal, 2021)
The article discusses the concept of open innovation as a model of interactive innovation management, which is a modern alternative to the traditional closed innovation approach. Three main models identified in the framework of this concept were characterized: centripetal (outside-in), centrifugal (inside-out) and mixed. Against this background the article presents the idea of crowd sourcing, which assumes the use of the wisdom of "the crowd" in the innovation process. These considerations were further supplemented with an analysis of the results of research carried out among Polish companies actively cooperating in the field of innovative activity with other entities in the years 2010-2012.